Workplace behavior of generation Z employees of Inspira Advisory and Consulting Limited - Irin, Fariha Yeasmin (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.